MAKNA FILOSOFIS SUNTIANG SEBAGAI HIASAN KEPALA TRADISIONAL WANITA MINANGKABAU - Husni, Nurul Izzati; Riza, Yulfira (Studi Budaya Nusantara, 2022)
Indonesia is a rich country. Indonesia not only has abundant natural wealth but also the richness of the diversity of tribes, cultures, nations, and languages adds to the wealth of Indonesia. These differences create unique diversity. Therefore, every nation has it's their customs and culture. In its implementation and use, it follows the prevailing traditions in the community where they live. Traditional clothing used by each region has its characteristics, one of which is indicated by traditional jewelry that carries its meaning and value. As for Minangkabau society, a woman when holding a wedding party (baralek) is given the title anak daro. At a wedding party, a anak daro wears traditional clothes with suntiang as traditional jewelry. Suntiang holds many philosophical values in it and symbolizes the greatness of the daro child. This paper aims to explain the meaning and philosophical value of suntiang for a woman who is getting married in Minangkabau. This research was conducted with a qualitative method that produces descriptive data and data collection techniques using library research techniques. The results of this study are known to the meaning and philosophical values contained in the Minangkabau suntiang.